PENGEMBANGAN E-MODUL BERBASIS NILAI KARAKTER PADA PEMBELAJARAN TEMA 2 SUBTEMA 2 DI KELAS V SDN 177 PEKANBARU - Nursa Indah; Febrina Dafit (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
E-modules are needed in development for students to understand the learning materials applied by teachers. The research is conducted to develop an E-Module and to determine the E-Module validity based on character values. This research is Research and Development with the ADDIE model, which is limited to the development stage. The validators of the research are two material aspect validators, two design aspect validators, and two language aspect validators. The research method of data collection used interviews, questionnaires, and documentation. The process of E-Modules development based on character values begins with the stage of need analysis, curriculum and materials, product design, and the validity process applied by the validator. Based on the validation results, the E-Module based on character values in theme 2 of sub-theme 2 learning at class V of SDN 177 Pekanbaru has achieved the criteria from design aspects 88%, material aspects 94%, and language aspects 92%. The overall average validity value is 91% with the category of very valid to use. Thus, it is recommended to apply E-Modules in order to find out how effective and practical E-Modules implementation is used during the learning process.